OPTIMIZING EDUCATIONAL REFORMS: A TEACHER DEVELOPMENT PROGRAM FOR GRADE 1 TEACHERS IN SANTA IGNACIA NORTH DISTRICT - Lingad, G. P. (International Journal of Current Practice in Management and Leadership (IJCPML), 2023)
The implementation of the K to 12 curriculum in the Philippines requires competent teachers who can effectively carry out the new requirements of the program. To assess the competencies of Grade 1 teachers in Santa Ignacia North District, this study was conducted with the aim of proposing a teacher development program based on the findings. The study revealed that the Grade 1 teachers were competent in their instruction, particularly in lesson planning, classroom management, and assessment of learning. However, some encountered problems in lesson planning, language difficulty, insufficient training on K to 12, and inadequate background in Mother Tongue concepts. These findings serve as a basis for identifying the strengths and weaknesses of teachers, enabling school heads to provide assistance, and alerting parents, communities, and government agencies of issues in implementing the curriculum. The proposed teacher development program aims to address these encountered problems through training programs, mentoring activities, and other initiatives. The program aims to enhance the instructional competence of Grade 1 teachers, leading to better teaching performance in implementing the K to 12 curriculum and improving the pupils' academic performance.